Walkout! : teacher militancy, activism, and school reform - D'Amico Pawlewicz, Diana (Research in educational policy., 2022)
"Teacher unions and their members have long stood as polarizing figures in a vast educational landscape. As in the Western films of the 1920s, policymakers, education reformers, and onlookers often assign union leaders and the teachers they represent either the white hats of heroes or the black hats of villains. Politicized efforts to reductively classify teacher unions as beneficial or dangerous have only served to obscure the extent to which labor militancy and teacher activism have become part and parcel of the American public school system and the primary mechanisms by which teachers' voices are heard - and heeded - in the policy arena. Teacher unions have grown in tandem with and in response to the expansion of the school bureaucracy and the acceleration of accountability reforms, and teachers' calls for recognition and reform are inseparable from broader movements for social change. Far more than either good or bad, teacher unions are the inevitable outgrowth of American public education as it stands today. This book offers an interdisciplinary exploration of the state of modern teacher unions, the complex spaces they operate in, and the connections between militancy, activism, and school reform. Breaking free from the white hat / black hat dyad that has for so long colored the lenses we use to understand unions, the chapters of this book engage a set of fundamental questions: Where did the modern moment of militancy come from, and in what ways is it a continuation or a departure from the approaches of previous organized teachers?; What is at stake in modern expressions of militancy for teachers, communities, and schools?; Beyond the flashpoint of the walkout, what is the effect of teacher activism?"--